The naked eye [large type] - Johansen, Iris; Johansen, Roy (Johansen, Iris. Kendra Michaels series., 2015)
"Kendra Michaels was instrumental in bringing serial killer Eric Colby to justice. And yet, despite his apparent execution at San Quentin, Kendra is convinced that Colby is still alive and framing her for murder. Suspicions mount and Kendra is thrust into deadly pursuit to clear her name and catch the killer no one believes exists anymore"--